Purification and regulatory properties of pyruvate kinase from Veillonella parvula. - Ng, S K (1975)
The nonglycolytic, anaerobic organism Veillonella parvula M4 has been shown to contain an active pyruvate kinase. The enzyme was purified 126-fold and was shown by disc-gel electrophoresis to contain only two faint contaminating bands. The purified enzyme had a pH optimum of 7.0 in the forward direction and exhibited sigmoidal kinetics at varying concentrations o-f phosphoenol pyruvate (PEP), adenosine 5'-monophosphate (AMP), and Mg-2+ ions with S0.5 values of 1.5, 2.0, and 2.4 mM, respectively. Substrate inhibition was observed above 4 m PEP. Hill plots gave slope values (n) of 4.4 (PEP), 2.8 (adenosine 5'-diphosphate), and 2.0 (Mg-2+), indicating a high degree of cooperativity. The enzyme was inhibited non-competitively by adenosine 5'-triphosphate (Ki = 3.4 mM), and this inhibition was only slightly affected by increasing concentration of Mg-2+ ions to 30 mM. Competitive inhibition was observed with 3-phosphoglycerate, malate, and 2,3-diphosphoglycerate but only at higher inhibitor concentrations. The enzyme was activated by glucose-6-phosphate (P), fructose-6-P, fructose-1,6-diphosphate (P2), dihydroxyacetone-P, and AMP; the Hill coefficients were 2.2, 1.8, 1.5, 2.1, and 2.0, respectively. The presence of each these metabolites caused substrate velocity curves to change from sigmoidal to hyperbolic curves, and each was accompanied by an increase in the maximum activity, e.g., AMP greater than fructose-1,6-P2 greater than dihydroxyacetone-P greater than glucose-6-P greater than fructose-6-P. The activation constants for fructose-1,6-P2, AMP, and glucose-6-P were 0.3, 1.1, and 5.3 mM, respectively. The effect of 5 mM fructose-1,6-P2 was significantly different from the other compounds in that this metabolite was inhibitory between 1.2 and 3 mM PEP. Above this concentration, fructose-1,6-P2 activated the enzyme and abolished substrate inhibition by PEP. The enzyme was not affected by glucose, glyceraldehyde-3-P, 2-phosphoglycerate, lactate, malate, fumerate, succinate, and cyclic AMP. The results suggest that the pyruvate kinase from V. parvula M4 plays a central role in the control of gluconeogenesis in this organism by regulating the concentration of PEP.